‘Even though it might take me a while, in the end, I understand it’: a longitudinal case study of interactions between a conceptual change strategy and student motivation, interest and confidence - McLure, Felicity; Won, Mihye; Treagust, David (2020)
Although there have been many investigations of the social, motivational, and emotional aspects of conceptual change, there have been few studies investigating the intersection of these factors with cognitive aspects in the regular classroom. Using a conceptual change approach, this case study reports experiences of a student of low to average prior attainment who achieved high levels of conceptual gains in five science topics over a two-year period. Her experience in the cognitive, social and affective domains was probed through analysis of interviews, student artefacts, video recordings of classroom learning, pre/post-tests and questionnaire results. For this student, peripheral or incidental persuasion of belonging to a supportive small group initially led to greater engagement with the construction of understanding through production of multiple student-generated representations, resulting in improved self-confidence and high levels of conceptual change. Evidence of transfer from performance to mastery approach goals, adoption of positive activating emotions and increased interest in science were observed. This study highlights that adoption of a multidimensional conceptual change approach with judicious organisation of small groups to support construction of verbal, pictorial and written representations of understanding may bring about changes in motivational stance, self-confidence and emotions to maximise conceptual change.